Processos formativos e reflexivos : contribuições para o desenvolvimento profissional de professores - Santos, Sydione (2008)
This research falls within the ambit of the ones that deals with teacher education, professional development and reflective practice. It is a study about teacher education processes, through a reflective and inquisitive orientation, carried out in a program designed for teachers in their teaching environment. It studies the contributions provided by a continuing professional development program at Curso Normal Superior com Mídias Interativas (Higher Education Course with Interactive Media) for the development of the teachers reflective process. The research objectives converge into analyzing the relation between teacher education process and the meaning of this process to teachers, considering the reflective practice. The research objectives were: to analyze the contributions of the teacher education program for teachers reflective process; to apprehend, analytically, the relation between the education provided and the level of reflection demonstrated by teachers about their professional conduct; to examine and analyze the moments and situations of teachers reflection during the formative program; to indicate the potentialities of the analyzed cases for new proposals for teacher education. Thus, through a descriptive and interpretative perspective, it was conducted a multiple study case, seeking to understand and explain teachers development and the meaning of each stage, which is part of a complex whole. The analysis was conducted through a longitudinal and an in-depth perspective in order to capture the reflective development process. The written narratives, related to the theoretical-practical activities, became the device of the research as well as a strategy within the context of the program. The research indicates the following: the teacher education processes are integrated in a movement of interdependence and interaction, which makes possible the relation between the teacher s knowledge, built by him/her as a student, and the projection of a new teacher practice, born from the theoretical and practical knowledge obtained during the program; there is a rapid development of the teachers inquisitive attitude as a result of the observation processes and the problematization, intrinsic to the period of investigative-reflective process; the theoretical and practical advance are related to activities of action research conducted in schools; the scientific theory articulates with teacher s experience interferes on how teachers analyze their practices; the manifestations of reflection cross with personal motivations and wishes as well as preview experiences. It is also possible to conclude that the ones that took part of this research manifested different and complementary reflection characteristics towards the nature of the developed proposals, the kind of narratives used, the pedagogical mediation, the personal way of guiding education in the program, the way how they see themselves in their professional career, the objectives that guide the teacher practice, the curricular time and space available to analyze experiences. It is considered that those kinds of proposals present potentialities to delineate actions to the academic, professional and continuing education.